CONTEXT AND MACHINE TRANSLATION (Journal of the College of Basic Education, 2022)
Briefly speaking, the study is intended to state explicit means for a linguist to cooperate with computer programmers in order to state as clear lexical data as possible so as to avoid translation errors and ambiguity. Such data include contextual relations to words surrounding a word in a sentence. The aim of the study is how to make a computer linguistically understand what we, humans, unconsciously do. This requires an explicit representation of the mental linguistic processes taking place in our own minds. One step in this direction is to rely upon context. It is to be resorted as a criterion to clarify the particular meaning wanted by SL, that is context is positioned as a judge to determine which of the meanings of a word (which has more than a meaning) to choose in such a context, and to determine which structure fits best as well.